Ketepatan Pengodean Diagnosis Pasien Klinik Penyakit dalam di RSAL Dr. Mintohardjo Jakarta Pusat 2021 - Endika Rachmad; Laela Indawati; Puteri Fannya; Lily Widjaja (Publikasi Indonesia, 2023)
Coding based on ICD-10 is the process of coding using letters and numbers that represent data components which aims to ensure the accuracy of the selected code representing the diagnosis designation established by the doctor, but in practice, there are still errors from the unclear writing of the diagnosis code. The purpose of this study was to get an overview of the accuracy of coding the diagnosis of Internal Medicine cases and identify the SOP for Code Giving at RSAL Dr. Mintohardjo. In this study, the author uses a quantitative descriptive method. The samples taken by the researchers were 100 which were obtained using the Slovin formula. From a total of 100 samples studied, there were 36 medical record data that were correct in coding and there were also 64 medical record data that were incorrect in coding. It can be concluded that the error in coding the diagnosis especially in internal medicine clinics at RSAL Dr. Mintohardjo is classified as high. Some errors in coding are caused by unclear writing of disease diagnoses, incomplete writing of disease diagnoses, inaccuracy in determining the main diagnosis, and lack of communication between the medical record officer in the coding section with nurses or doctors.